PHARMACOLOGICAL ACTIVITY OF SPINACIA OLERACEA LINN.- A COMPLETE OVERVIEW - Metha, Deven; Belemkar, Sateesh (Asian Journal of Pharmaceutical Research and Development, 2014)
Herbal and natural products of traditional medicine have been used for centuries in every culture throughout the world. Medical professionals and Scientists have shown increased interest in this field as they diagnose the true health benefits of these remedies. “Let food be your medicine and let medicine be your food” was advised by the father of medicine, Hippocrates, over two million ago. It’s still true today that “you are what you eat.” Spinach is a leafy green vegetable that came originally from south-western Asia and is now grown in most parts of the world. Scientifically it is known as SpinciaoleraceaLinn. (Family-Chenopodiaceae). Though Spinach is most often used as a food, it has medicinal value as well. Spinach is packed with vitamins such as vitamin C, vitamin A and vitamin E and minerals like magnesium, manganese, iron, calcium and folic acid. Spinach is also a good source of chlorophyll, which is known to aid in digestion. Spinach is also rich in the carotenoids beta-carotene and lutein. It is a good source of the bioflavonoid quercetin with many other flavonoids which exhibits anti-oxidant, ant proliferative, anti-inflammatory, antihistaminic, CNS depressant, protection against gamma radiation, hepatoprotective properties in addition to its many other benefits. Spinach is also used to prevent the bone loss associated with osteoporosis and for its anti-inflammatory properties in easing the pain of arthritis. Spinach is good for the heart and circulatory system and has energy-boosting properties. Spinach is truly one of nature's most perfect foods.